ANALISIS TINDAK PIDANA KORUPSI DALAM PENGADAAN BARANG DAN JASA OLEH PEMERINTAH (KASUS PENGADAAN VIDEOTRON; PUTUSAN PENGADILAN NEGERI JAKARTA PUSAT NOMOR : 36/PID.SUS/TPK/2014/PN.JKT.PST.): Rahimah - admin, admin; Hariz Hamdallah, Muhammad Andika (Fakultas Hukum Universitas Islam Jakarta, 2018)
The criminal act of procurement of videotron in this case, Decision Number: 36/PID.SUS/TPK/2014/PN.JKT.PST. This study aims to determine the legal arrangements for the application of criminal sanctions under special minimum threats in cases of criminal acts of corruption in the procurement of goods and services by the government and to find out the basis of judges' considerations to apply sanctions of corruption in the procurement of goods and services by the government. The research method used is the yuridical normative. The conclusion of this study shows that positive legal arrangements regarding the application of criminal sanctions under a special minimum threat in cases of criminal acts of corruption in the procurement of goods and services by the government Based on Decision Number: 36/PID.SUS/TPK/2014/PN.JKT.PST. note that firstly, regulated and threatened with criminal offense in the Subsidair indictment: Article 3 jo. Article 18 Article 18 of Law Number 31 of 1999 concerning Eradication of Corruption, as amended by Law Number 20 of 2001 concerning Eradication of Corruption Jo. Article 55 paragraph (1) 1 of the Criminal Code. As well as convicting the defendant with imprisonment for 2 (two) years and 6 (six) months reduced for the duration of the defendant's detention with the order that the defendant remain detained in detention and a criminal fine of Rp. 50,000,000 (fifty million rupiahs) in 6 (six) months confinement. Secondly, the basic considerations of judges to apply unfair sanctions of Article 2 paragraph (1), because Defendant Hendra Saputra is actually a tool used by witness Riefan Avrian in fulfilling his intention to participate in and win Videotron procurement work at the Ministry of Cooperatives and Small Medium Enterprises Building RI in 2012.